When I was a turkey : based on the Emmy award-winning PBS documentary My life as a turkey - Hutto, Joe; Guiberson, Brenda Z. (Henry Holt and Company, 2017)
When I Was a Turkey is a middle-grade adaptation of the remarkable true story of a naturalist who raised a flock of wild turkeys using imprinting.